Analyzing Content Promotion Strategies on a Marketplace: A Social Network Study: Studi Analisis Jaringan Sosial Strategi Promosi Konten di Platform Marketplace - Hafif Wisnu Wahyudi; Rita Ambarwati Sukmono (Academia Open, 2023)
This study aims to examine the user response to content promotion strategies on Bukalapak Marketplace, focusing on interactions related to discounts, free shipping, and cashback. Qualitative research methods were employed, using data collected from Twitter through data pulling and processed using Wordij and Gephi for data filtering. Social Network Analysis (SNA) with Crawl Data was applied to determine the map of interactions on the platform. The results revealed that user response varied across different promotional strategies and time periods. Specifically, the most frequent user response was observed for content promoting "free shipping" during 2020-2021, while "cashback" promotions were less often responded to. These findings have implications for marketers and platform managers in optimizing content promotion strategies to effectively engage users and enhance marketing outcomes. Highlights: User engagement: Analyzing the response of users to content promotion strategies on a marketplace platform using Social Network Analysis. Effective marketing tactics: Investigating the impact of different promotional approaches such as discounts, free shipping, and cashback on user engagement. Optimization for engagement: Identifying the most and least successful content promotion strategies based on user response and implications for enhancing marketing outcomes. Keywords: Content promotion, Marketplace platform, User response, Social Network Analysis, Marketing strategies